Determinant Factors of Profitability of the Indonesian Non-Financial SMEs PEFINDO Index - Farel, Jose Raci; Farah Margaretha Leon; Yosephina Endang Purba (Jurnal Economic Resource, 2024)
This research aims to determine the influence of determinant factors of non-financial SMEs' PEFINDO index profitability in Indonesia from 2018 to 2022, with independent variables including company size, company age, company efficiency, working capital, liquidity, leverage, volatility, and market risk on the dependent variables of ROE and ROA. The study utilizes secondary data in the form of financial reports from non-financial companies that have been included in the PEFINDO25 index of the Indonesia Stock Exchange during the 2018-2022 period. This research sample used purposive sampling and obtained 65 companies as samples. Data analysis for hypothesis testing involves multiple regression using E-views 9 software. The test results indicate that company size, company efficiency, and working capital have a positive impact on ROE, while company age, leverage, and market risk have a negative impact on ROE. Company size, company age, and volatility have a negative impact on ROA, while company efficiency and working capital have a positive impact on ROA. However, liquidity does not significantly affect either ROE or ROA. These factors need to be considered by companies to make informed decisions in maintaining or improving company profitability, avoiding financial distress leading to bankruptcy, and determining suitable investments for investors.